Analysis of Multi-Pin Modular Daughterboard-to-Backplane Connectors at High Bit Rate Signals - C. N. Capsalis; C. P. Chronopoulos; J. G. Tigelis; N. K. Uzunoglu (Active and Passive Electronic Components)
A theoretical model for the electrical characterization of multi-pin modular daughterboard-to-backplane connectors at high bit rate signals is developed. The fundamental field equations are transformed into a linear system of equations for the currents and voltages at the edges of the pins of the connector.